2013
DOI: 10.1038/onc.2013.6
|View full text |Cite
|
Sign up to set email alerts
|

p53 promotes repair of heterochromatin DNA by regulating JMJD2b and SUV39H1 expression

Abstract: Constitutive heterochromatin is important for maintaining chromosome stability but also delays the repair of DNA double strand breaks (DSB). DSB repair in complex mammalian genomes involves a fast phase (2–6 hrs) where most of the breaks are rapidly repaired, and a slow phase (up to 24 hrs) where the remaining damages in heterochromatin are repaired. We found that p53 deficiency delays the slow phase DNA repair after ionizing irradiation. P53 deficiency prevents down regulation of histone H3K9 trimethylation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 58 publications
(84 reference statements)
7
57
0
Order By: Relevance
“…Moreover, we demonstrated that despite reduced DBS repair, as assayed by ␥H2AX foci, the Suv39h1/h2-dn cells display an increased tolerance to ␥-irradiation-induced DNA damage. This is consistent with a recent report by Zheng et al (60) demonstrating that overexpression of Suv39h1 increased sensitivity to ␥-irradiation. Taking into account the increased genomic instability and tumor-prone phenotype associated with Suv39h1/h2 deficiency (16 -18), it is possible that reductions in H3K9me3 confer an increased tolerance to DNA damage.…”
Section: Volume 288 • Number 29 • July 19 2013supporting
confidence: 83%
“…Moreover, we demonstrated that despite reduced DBS repair, as assayed by ␥H2AX foci, the Suv39h1/h2-dn cells display an increased tolerance to ␥-irradiation-induced DNA damage. This is consistent with a recent report by Zheng et al (60) demonstrating that overexpression of Suv39h1 increased sensitivity to ␥-irradiation. Taking into account the increased genomic instability and tumor-prone phenotype associated with Suv39h1/h2 deficiency (16 -18), it is possible that reductions in H3K9me3 confer an increased tolerance to DNA damage.…”
Section: Volume 288 • Number 29 • July 19 2013supporting
confidence: 83%
“…11,50,51 Nucleolus itself is a good example of how transcription, chromatin remodeling, and DNA repair might go together. Cockayne syndrome B (CSB) protein is a DDR factor involved in the early steps of transcriptioncoupled NER that is also important in the regulation of rRNA gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of mTOR using rapamycin blocks senescence and keeps cells in a state of reversible quiescence after p21 overexpression (Demidenko et al 2009). p53 also represses the expression of histone H3K9 methylase SUV39H1 and induces histone demethylase JMJD2d, which may prevent the establishment of stable gene silencing (Zheng et al 2013). Therefore, cellular context and pathway cross talk may determine whether cells commit to irreversible cell-cycle arrest.…”
Section: Cell Fate Decision Between Arrest and Senescencementioning
confidence: 99%
“…Furthermore, p53 regulates genes involved in heterochromatin formation to facilitate the timely repair of DNA strand breaks in constitutive heterochromatin regions. p53-null cells have deficiencies in the repair of doublestrand breaks in heterochromatin and have reduced long-term viability after ionizing irradiation (Zheng et al 2013).…”
Section: Cell-cycle Checkpoint Functions Of P53mentioning
confidence: 99%